Respuesta :

The value of P in the expression [tex]x^2-10x+P=(x-A)(x-B)[/tex] is 25

Given the expression [tex]x^2-10x+P=(x-A)(x-B)[/tex]

To get the value of P, we will use the completing the square method;

Add the square of the half of the coefficient of x

  • The coefficient of x is -10
  • Half of the coefficient of x is -10/2 = 5
  • Square of half of the coefficient of x = 5^2 = 25

Hence the complete quadratic expression will be [tex]x^2-10x + 25[/tex]

Hence the value of P in the expression [tex]x^2-10x+P=(x-A)(x-B)[/tex] is 25

Learn more here: https://brainly.com/question/13981588